Rare Diseases in Neurology — Caring for a Patient with Pompe’s Disease - Anna Roszmann; Mikołaj Hamerski; Marcelina Skrzypek-Czerko (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Pompe disease, a severe metabolic myopathy, is caused by mutations in the gene coding for acid alpha-glucosidase (GAA), what lead to intralysosomal accumulation of glycogen in all tissues, most notably in skeletal muscles. Pompe disease was the first documented lysosomal storage disease, nowadays we know around 60 similar disorders. Aim. Presentation of the clinical picture of a man with Pompe’s disease. Case Report. A man at the age of 40, diagnosis of the Pompe’s disease was made only at the age of 31. The first symptoms, indicating the patient’s development of the disease, were already present in the early school age. At first, the clinical picture presented by the patient led to the diagnosis of muscular dystrophy. Discussion. Pompe disease presents as a continuum of clinical phenotypes that differ by age of onset, severity, and organ involvement. Pompe disease affects people of all ages with varying degrees of severity. Two main broad types are recognized based on the onset of symptoms and the presence or absence of cardiomyopathy. Infantile onset Pompe disease (IOPD) as one, and the most severe for mod the disease. Other and less destructive is late-onset Pompe disease (LOPD) manifests any time after 12 months of age. The disease can be successfully treated by enzyme replacement therapy with alglucosidase alfa that was approved for human use in 2006. Conclusions. In big importance is nurses role as educators and support for the patients during their hospitalizations for medicine infusions twice a month. It time when the knowledge and significance of proper life style can be discussed and implemented to empower the patients. (JNNN 2019;8(4):170–176)